Peasants, Political Police, and the Early Soviet State - Hudson, H. author. aut Link
XIII, 177 p.
Keywords: This book combines social and institutional histories of Russia, focusing on the secret police and their evolving relationship with the peasantry. Based on an analysis of Cheka/OGPU reports, it argues that the police did not initially respond to peasant resistance to Bolshevik demands simply with the gun—rather, they listened to peasant voices.